1991
DOI: 10.1192/bjp.158.1.93
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Child Psychiatry Liaison Service on Patterns of Referral

Abstract: A retrospective study of referrals to a child psychiatry liaison service was carried out in order to assess the impact of the reorganisation of the service. A total of 55% of referrals were of in-patients on the paediatric ward; other in-patients made up 12.5%. Of all referrals, 67% were from paediatricians. Of the children who had not harmed themselves, most were referred either for help with the management of physical illness or for investigation of a non-organic physical complaint. The main finding was that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…The advocated provision of a hospital‐based paediatric–psychiatric liaison service (Black et al . 1990; McFadyen et al . 1991; Garralda 1994; 2001) would clearly help to address this need and increased opportunities for paediatricians to train in child psychiatry should also be given priority.…”
Section: Discussionmentioning
confidence: 99%
“…The advocated provision of a hospital‐based paediatric–psychiatric liaison service (Black et al . 1990; McFadyen et al . 1991; Garralda 1994; 2001) would clearly help to address this need and increased opportunities for paediatricians to train in child psychiatry should also be given priority.…”
Section: Discussionmentioning
confidence: 99%
“…Stocking et al (1972) reported that almost two‐thirds of children admitted to paediatric wards would have benefited from child psychiatric consultation. Paediatricians are increasingly recognising the need for help in the diagnosis and treatment of mental health problems in sick children and their families, and making use of the available resources (Rothenberg, 1979; McFadyen, Broster, and Black, 1991). Kurtz, Thornes and Wolkind (1994) highlighted in their 1993 UK survey the range of professionals involved in working with young people with mental health problems and their lack of awareness of mental health issues generally.…”
Section: Introductionmentioning
confidence: 99%
“…No trabalho de "liason", o psiquiatra de crianças e adolescentes envolve-se mais diretamente no atendimento do paciente, inclusive atuando como membro da equipe. [1][2][3][4] A interconsulta em pediatria iniciou-se com Léo Kanner 5 na década de 30 no John's Hopkins Hospital. Atualmente, a maioria dos hospitais de médio e grande porte nos Estados Unidos conta com serviços de interconsulta.…”
Section: Introductionunclassified
“…5 Dados quanto à diminuição do tempo de recuperação e de hospitalização, bem como quanto à maior aderência ao tratamento em pacientes beneficiados pelo serviço de interconsulta, confirmam a relevância deste trabalho. 2,6 Abrangência da interconsulta psiquiátrica na pediatria A interconsulta psiquiátrica dirigida à pediatria abrange a assistência à criança e ao adolescente, assim como a seus pais, familiares e equipes envolvidas no cuidado destes pacientes.…”
Section: Introductionunclassified